Antibiotic-resistant bacteria in bovine milk in India - Sahoo, Sonali; Behera, Manas Ranjan; Mishra, Biswajit; Sahoo, Priyadarshini; Kar, Sonali (Journal of Advanced Veterinary and Animal Research, 2023)
Antibiotic resistance (ABR) is a global issue that draws the attention of all healthcare experts in the veterinary and medical fields. Of various factors, indiscriminate and unregulated antibiotic usage in the animals reared for food production, especially in cows and buffaloes suffering from mastitis, contribute significantly to the rising incidence of resistant bacteria. A literature survey reveals the spread of resistant strains of mastitis-causing bacteria, like Staphylococcus aureus and Escherichia coli, to humans. In addition, antibiotic residues detected in milk samples against all major groups of antibiotics are likely to enter the human body through the food chain and aggravate the condition. The cumulative effects of ABR have emerged as a silent killer. The benefits of systematic surveillance on ABR in India are yet to be available. Here is an attempt to understand the ABR burden in India associated with bovine milk and its mitigation strategies. J. Adv. Vet. Anim. Res., 10(1): 21–29, March 2023 http://doi.org/10.5455/javar.2023.j648